Hierarchical N-doped graphene coated 1D cobalt oxide microrods for robust and fast lithium storage at elevated temperature. (1st July 2019) - Wu, Naiteng; Shen, Jinke; Sun, Li; Yuan, Mengyuan; Shao, Yanyan; Ma, Jiaming; Liu, Guilong; Guo, Donglei; Liu, Xianming; He, Yan-Bing
Abstract: The practical applications of metal oxides in lithium-ion batteries require the robust and fast lithium storage performance in the wide temperature range. Construction of the suitable structure is still considered as an important approach to address metal oxide anode issues (volume expansion and inferior conductivity). Herein, an electrostatic adsorption-carbothermic reduction process is developed to prepare 1D hierarchical CoO@N-doped graphene microrods (CoO@N-rGO). 1D hierarchical microrod-like structure coated by a uniform & tight N-doped graphene not only builds up a bifunctional conductive path for Li + and electrons, but also enhances the ability to accommodate the volumetric change. Oxygen vacancies caused by incomplete reduction of Co 3+ would accelerate the kinetic process of conversion reaction. Moreover, a dominant pseudocapacitive effect (80.06%) induced by above structural features ensures the fast lithium storage properties. When served as anode material in LIBs, the as-prepared CoO@N-rGO manifests the high reversible capacity of 1588 mAh g −1, excellent long-term cycling stability under high current density (948 mAh g −1 after 500 cycles at 2 A g −1 ). Particularly, due to the reduced side-reaction between electrolyte and modified electrode, the CoO@N-rGO retains a reversible capacity of 1164 mA g −1 after 1000 cycles under 1 A g −1 at 55 °C. Graphical abstract: Image 1 Highlights: CoO@N-rGO microrods exhibit the excellent cyclic stability at 55 °C. An electrostatic adsorption-carbothermic reduction process is presented. Pseudocapacitive contribution is dominated in the lithium storage process.